Flow-induced Vibration of Flexible Bottom Wall in a Lid-driven Cavity - Sun, Xu; Li, Wenxin; Ye, Zehua (Journal of Vibration Testing and System Dynamics, 2026)
Flow-induced vibration of the flexible bottom wall in a lid-driven cavity is investigated numerically using a well-validated finite element scheme for fluid-structure interaction (FSI). First, the mechanical and mathematical models of a lid-driven cavity with flexible bottom are presented, and the corresponding FSI solution procedure is introduced briefly. Then, the accuracy and stability of the developed FSI scheme and code are examined and a grid independence test is carried out. Finally, using very fine increment, bifurcations of the flow-induced vibration (FIV) of the flexible bottom with respect to the structure rigidity and Reynolds number are studied in detail. The results could reveal more details of the benchmark FSI model involving a lid-driven cavity with flexible bottom, gaining a better understanding on other FIVs caused by the internal unsteady flows.